2017
DOI: 10.3174/ajnr.a5327
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Imaging of Venous Side Cerebral Small-Vessel Disease in Older Adults: An MRI Method at 7T

Abstract: BACKGROUND AND PURPOSE:Traditional neuroimaging markers of small-vessel disease focus on late-stage changes. We aimed to adapt a method of venular assessment at 7T for use in older adults. We hypothesized that poorer venular morphologic characteristics would be related to other small-vessel disease neuroimaging markers and a higher prevalence of small-vessel disease-Alzheimer disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Second, the deep capillary plexus is aligned along the course of the macular venules and drain into the superficial venules ( 20 ) and has been suggested to be involved in the venous side of circulation ( 21 ). Previous literature using the fundus camera reported on venular widening in patients with WMH ( 22 24 ); Ikram et al ( 25 ) showed that larger venular diameters were associated with the progression of WMH, while De Jong et al ( 26 ) reported that venular widening reflects lower arteriolar oxygen saturation and suggested that venular diameter reflects a lower oxygen supply to the brain. Since changes in the DCP were significantly different among the two groups, our results suggest that the DCP reflects the lower oxygen saturation and also indicates the progression of the disease as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the deep capillary plexus is aligned along the course of the macular venules and drain into the superficial venules ( 20 ) and has been suggested to be involved in the venous side of circulation ( 21 ). Previous literature using the fundus camera reported on venular widening in patients with WMH ( 22 24 ); Ikram et al ( 25 ) showed that larger venular diameters were associated with the progression of WMH, while De Jong et al ( 26 ) reported that venular widening reflects lower arteriolar oxygen saturation and suggested that venular diameter reflects a lower oxygen supply to the brain. Since changes in the DCP were significantly different among the two groups, our results suggest that the DCP reflects the lower oxygen saturation and also indicates the progression of the disease as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…With aging, the ability of the oligodendrocytes to regenerate myelin sheaths decreases [40] . To what degree pallor represents loss of myelin sheaths or loss of myelin secondary to axonal loss remains unresolved [44] . In aged primates, cognitive impairment exacerbated by hypertension is associated with myelin damage and microglial changes within the white matter ( Box 3 ).…”
Section: Neuropathological Changes That Underlie Wmhsmentioning
confidence: 99%
“…An early cerebral microvascular study observed that arterioles become more tortuous in some of SVD earlier states [80]. The visualization of the venous side of the cerebral microvascular pathology was not possible without contrast; therefore, the alterations of the venules due to small vessel disease were rarely investigated and thus poorly understood [81]. The increase in susceptibility (T2*) at the Ultrahigh field (7 T) MR imaging enables the visualization of venous microcirculation [82, 83].…”
Section: Neuroimaging Of Microvascular Mechanism In Small Vessel Diseasementioning
confidence: 99%